Functional Outcome of Solid Intramedullary Interlocking Nail in Tibial Diaphyseal Fractures - Bhandari, Pratap Babu; Karki, Dhan Bahadur; Bisht, Rishi; Serchan, Binod (Nepal Orthopaedic Association Journal, 2021)
Background: Tibial diaphyseal fractures are of high concern nowadays, both due to their increasing incidence as a result of motor vehicle accidents and also due to the high rate of associated complications. Closed intramedullary nailing is the treatment of choice in stabilizing displaced diaphyseal fracture of tibia. This study aims to evaluate functional outcome of solid intramedullary interlocking nail in tibial diaphyseal fractures.Method: This is a prospective observational study from June 2015 to December 2016 done in National Trauma Center, Kathmandu among 30 patients having closed or Gustilo type I and II open fractures. All fractures were fixed with solid intramedullary interlocking (SIGN) nail and followed clinically and radiologically for union and for any complications. Modified Johner and Wruh’s criterion was used to assess functional outcome.Result: 80% cases were males. Mean age was 32.16 years (range = 18-72 years). Road traffic accident was the most common cause (60%). 46.7% were closed fractures and 33.3% were comminuted or segmental. 40% had distal third fracture and fibula was also involved in 70% cases. Mean time for radiological union was 14 weeks and clinical union was 10 weeks. 30% had mild anterior knee pain which was managed with analgesics. 10% had mild superficial infection, which was managed with antibiotics. Excellent, good, fair and poor results were obtained in 66.67%, 10%, 13.33% and 0% cases respectively.Conclusion: Solid intramedullary interlocking nailing for closed tibial diaphyseal fracture has excellent outcomes. It can be performed without fluoroscopy. It provides high rate of union, less complications and early return to function.